A review of recent advances on single use of antibody-drug conjugates or combination with tumor immunology therapy for gynecologic cancer - Wang, An-Jin; Gao, Yang; Shi, Yu-Ying; Dai, Meng-Yuan; Cai, Hong-Bing (Frontiers in Pharmacology, 2022)
Immune checkpoint inhibitors (ICIs) have made significant progress in the treatment of various cancers. However, due to the low ICI responsive rate for the gynecologic cancer, ICI two-drug combination therapy tends to be a predominant way for clinical treatment. Antibody-drug conjugates (ADCs), a promising therapeutic modality for cancer, have been approved by the FDA for breast cancer, lymphoma, multiple myeloma and gastric cancer. On September 2021, the FDA granted accelerated approval to tisotumab vedotin for patients with recurrent or metastatic cervical cancer. Currently, the role of therapy of ADCs on gynecologic tumors was also included in medication regimens. Now more than 30 ADCs targeting for 20 biomarkers are under clinical trials in the field, including monotherapy or combination with others for multiple lines of therapy. Some ADCs have been proved to enhance the antitumor immunity effect on both pre-clinical models and clinical trials. Therefore, combination of ADCs and ICIs are expected in clinical trials. In this review, we discuss current development of ADCs in gynecologic oncology and the combination effects of ICIs and ADCs.